Uncovering the Nexus Between Cooperative Learning Contexts and Achievement Goals in Physical Education. Issue 4 (August 2021) - Rivera-Pérez, Sergio; Fernandez-Rio, Javier; Gallego, Damián Iglesias
Cooperative learning is a pedagogical framework extensively used in educational contexts worldwide, but some scholars warn that we do not know much about how its claimed outcomes are delivered. The aim of this study was to uncover the connections between cooperative learning contexts and students' task and self-approach goals in physical education. We hypothesized that those students who perceived a stronger cooperative learning context in their classes would also show higher task and self-approach goals. A total of 1328 students (648 females and 680 males) from three different educational stages: primary education (n = 584), secondary education (n = 550) and baccalaureate (n = 194), agreed to participate. Participants' ages ranged between 10 and 20 years ( M = 13.11; SD = 2.45). An ex-post-facto, cross-sectional research design was followed. Results showed a direct and significant connection between high-perceived cooperative learning contexts and high students' task and self-approach goals. The odds ratio tests verified this positive association, indicating a 4-times greater probability for students who perceived a strong cooperative learning context in the classroom of having high task and self-approach goals. In the same line, we observed that, as the perception of a cooperative learning context increased, task and self-approach goals also increased. This means that a small change in the class context to make it more cooperative had an impact on the students' achievement goals. Teachers should try to create class contexts where students perceive a strong cooperative learning climate, because it has been connected to adaptive motivational patterns, task and self-approach goals, and these are associated with positive outcomes.